Encouraging Learner Independence - Hector Low (Asociación Colombiana de Profesores de Ingles, 2016)
My aims in this paper are to look at what learner independence means and then to focus on some ways of encouraging it, developing the students' awareness of what is involved and how to go about the process of achieving more autonomy. I will draw on my personal experience and the work we are doing in the British Council in Bogotá on learner training and fostering good learning habits.